Testing the elite : Yale College in the Revolutionary era, 1740-1815 - Wilock, David (New York : Routledge, 2024)
"This volume explores the extent to which the Revolutionary period (1740-1815) impacted the faculty, students, and institutional life of Yale College, and how those changes shed insight into the nature of the American Revolution itself as a conservative or radical event. Throughout the 18th century, Yale continued a tradition of producing individuals who would perpetuate the economic and social status quo. At the same time, the institution was undergoing an evolution reflective of the broader movements in America that would persist into the era of the early republic. In order to examine Yale's influence on those who attended, this study uses the student experience as a major source of evidence. Yale's curriculum and culture prior to 1776 were beginning to embrace Enlightenment ideas, though not fully and due in no small part to the petitions of students. From literary societies to student militias, there were ways for students to engage in an exchange of ideas about new courses and new modes of national government outside the classroom. The book is intended for both undergraduates and graduate students as well as general readers who are interested in the history of higher education, the American Revolutionary era, and the history of Connecticut"--
The Presidents of Yale -- The Backbone of Yale: Staff, Faculty, and Curriculum and Instruction -- Resisting Regimentation: The Yale College Student Experience -- Conclusion: Yale at the Dawn of the Nineteenth Century.
Keywords: Yale College (1718-1887) -- History; Yale College (1718-1887) -- Presidents; Yale College (1718-1887) -- Students -- Intellectual life -- 18th century; Radicalism -- United States -- History -- 18th century; Connecticut -- History -- Colonial period, ca. 1600-1775.; Connecticut -- History -- Revolution, 1775-1783.; Connecticut -- History -- 1775-1865.; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States -- History -- Confederation, 1783-1789.; HISTORY / General; HISTORY / Modern / General; HISTORY / Social History